Antecedents, mediators and consequences of sustainable operations: A framework for analysis of the manufacturing industry. Issue 7 (28th January 2019) - De Guimarães, Julio Cesar Ferro; Dorion, Eric Charles Henri; Severo, Eliana Andréa
Abstract : Purpose: The purpose of this paper is to propose a framework for analyzing the relationships between the antecedent factors, mediators and consequences of sustainable operations (SO), which can be applied for empirical studies in the manufacturing industry. Design/methodology/approach: Based on the importance of identifying the determinants of SO, a qualitative and exploratory research was developed through an extensive review of the literature. Findings: The main theoretical contribution of this research on organizational studies is the SO analysis proposition framework, which allows the elaboration of scales, based on observable variables of each factor, as well as evaluating the influence intensity of the relations between the constructs. Research limitations/implications: The proposed framework of this research was developed to analyze companies of the manufacturing industry. In order to use the proposed framework in other industries (commerce, services), it will be necessary to make adaptations and adjustments on the observable variables and constructs. Originality/value: The paper has an important theoretical value in proposing scales for the SO factors and can be useful for future quantitative approach and surveys. Consequently, the researcher will be able to evaluate the scales of the factors and the intensity of the relations between observable variables in the formation of the constructs, as well as the intensity of influence among the constructs.